A Redox Cu(II)-Graphene Oxide Modified Screen Printed Carbon Electrode as a Cost-Effective and Versatile Sensing Platform for Electrochemical Label-Free Immunosensor and Non-enzymatic Glucose Sensor - Phetsang, Sopit; Khwannimit, Duangruedee; Rattanakit, Parawee; Chanlek, Narong; Kidkhunthod, Pinit; Mungkornasawakul, Pitchaya; Jakmunee, Jaroon; Ounnunkad, Kontad (Frontiers in Chemistry, 2021)
A novel copper (II) ions (Cu(II))-graphene oxide (GO) nanocomplex-modified screen-printed carbon electrode (SPCE) is successfully developed as a versatile electrochemical platform for construction of sensors without an additionally external redox probe. A simple strategy to prepare the redox GO-modified SPCE is described. Such redox GO based on adsorbed Cu(II) is prepared by incubation of GO-modified SPCE in the Cu(II) solution. This work demonstrates the fabrications of two kinds of electrochemical sensors, i.e. a new label-free electrochemical immunosensor and non-enzymatic sensor for detections of immunoglobulin G (IgG) and glucose, respectively. Our immunosensor based on square-wave voltammetry (SWV) of the redox GO-modified electrode shows the linearity in a dynamic range of 1.0-500 pg.mL-1 with a limit of detection (LOD) of 0.20 pg.mL-1 for the detection of IgG while non-enzymatic sensor reveals two dynamic ranges of 0.10-1.00 mM (sensitivity = 36.31 μA.mM-1.cm-2 and 1.00 - 12.50 mM (sensitivity = 3.85 μA.mM-1.cm-2) with a LOD value of 0.12 mM. The novel redox Cu(II)-GO composite electrode is a promising candidate for clinical research and diagnosis.